Factors associated with COVID-19 vaccine hesitancy amongst refugees in Australia. Issue 1 (1st January 2021) - Liddell, Belinda J.; Murphy, Stephanie; Mau, Vicki; Bryant, Richard; O'Donnell, Meaghan; McMahon, Tadgh; Nickerson, Angela
ABSTRACT: Background: Refugees may be especially vulnerable to the adverse effects of COVID-19. Therefore it is critical that refugee communities are supported to access COVID-19 vaccines and for public health responses to address vaccine hesitancy. Objective: To investigate the key demographic factors, barriers and attitudes associated with vaccine hesitancy in a community sample of refugees. Method: Participants in the Refugee Adjustment Study, a cohort of refugees living in Australia, were invited to complete a survey about their COVID-19 vaccine intentions, barriers to access and attitudes relating to the vaccine. Results: Of the 516 participants, 88% were unvaccinated and 28.1% were classed as vaccine hesitant. Key predictors of vaccine hesitancy were younger age, information and trust barriers, lower logistical barriers, and attitudes relating to low control and risk posed by COVID-19. Conclusions: Findings suggest that public health strategies need to address trust, control and risk perception attitudes to increase COVID-19 vaccine uptake in resettled refugee communities. HIGHLIGHTS: Low trust in health authorities, concerns about a lack of control, and the perception of COVID-19 as low-risk emerged as the salient barriers and attitudes associated with COVID-19 vaccine hesitancy in a trauma-exposed refugee sample.